Automatic Grounding Protection Technology for Low-Voltage Cable in Distribution Network Without Power Outage. Issue 4 (May 2021) - Zou, Kemin; Li, Shengquan; Zou, Hanfeng; Xu, Cuishan; Feng, Zehua; Shao, Yuanpeng
Abstract: With the continuous development of science and technology, the current era of low-voltage cable equipment has changed earthshaking compared with the traditional power failure equipment, and has a more significant application in the distribution network control system, effectively improve the work efficiency of power failure equipment. The rapid development of high voltage technology also provides a platform for the application of low voltage cable equipment. By expatiating the characteristics and present situation of the low-voltage cable equipment, this paper analyzes the application problems in the design of the non-power outage equipment system, and puts forward practical suggestions for readers' reference.